Effect of 20km simulated race load on propulsive forces during ski skating - Ohtonen, O.; Linnamo, V.; Göpfert, C.; Lindinger, S. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
Biomechanics of skate skiing has been of interest since the late 80`s after the skating technique was introduced to cross-country (XC) ski racing. When considering how forces produced during skating skiing actually propels the athlete forward a methodological approach beyond detecting of ground reaction forces is needed Propulsion calculation from skate skiing was done already in the 90`s (Smith, 2003). Since then the model for calculating propulsion has slightly been modified while pressure insoles and instrumented roller skis have been used (Stöggl & Holmberg, 2015, Hoset et al., 2014). Most recent modifications to propulsion calculations were presented by Göpfert et al. (2017) where pole forces and 3D leg forces were used and the effect of propulsion to the center of mass (COM) is analysed. The aim of this simulated race study was to find out how accumulated fatigue during a race affects athlete`s performance and ability to produce propulsion with the upper as well as the lower body. We hypothesized that the arms will be more fatigued compared to legs in terms of propulsion decrease after the race.